Buoyancy-driven natural ventilation in one storey connected with an atrium. Issue 4 (2nd October 2019) - Gong, Jian; Hang, Jian
Abstract: A macroscopic zone model is used to analyze buoyancy-driven natural ventilation in one storey connected with an atrium. The height ratio between the storey and atrium can be variable as well as the heat ratio between the two heat sources, one in storey and the other in atrium. Both the steady-state and time-dependent flow rate through the storey and atrium are investigated. The transient process from different initial conditions to different steady-state flow patterns are numerically performed by means of Euler method, especially the detailed investigation of time evolution of flow rate between different flow patterns from 'zero' initial conditions. Seven classical cases of time development flow rate are given to explain flow pattern can evolve from one to another and the implications of natural ventilation driven by the two opposing buoyancy forces in atrium building are discussed. Furthermore, small-scale experiments were conducted to evaluate switch of flow pattern in transient flow. Stability analysis and bifurcation point of multiple flow patterns are also considered on the basis of fundamental nonlinear dynamics.